Sensors and Instrumentation, Aircraft/Aerospace and Energy Harvesting , Volume 8 Proceedings of the 36th IMAC, A Conference and Exposition on Structural Dynamics 2018 - Wee Sit, Evro; Walber, Chad; Walter, Patrick; Wicks, Alfred; Seidlitz, Steve (Conference Proceedings of the Society for Experimental Mechanics Series, 2019)
Sensors and Instrumentation, Volume 8.  Proceedings of the 36th IMAC, A Conference and Exposition on Structural Dynamics, 2018, the eighth volume of nine from the Conference brings together contributions to this important area of research and engineering.  The collection presents early findings and case studies on fundamental and applied aspects of Sensors and Instrumentation, including papers on: Sensor Applications Accelerometer Design Accelerometer Calibration Sensor Technology Energy Harvesting Technology Aircraft/Aerospace Technology.